Structural basis for VPS34 kinase activation by Rab1 and Rab5 on membranes - Shirley Tremel (Nature Portfolio, 2021)
The phosphatidylinositol-3-phosphate (PI3P) is generated by the lipid kinase VPS34, in the context of VPS34 complex I on autophagosomes or complex II on endosomes. Biochemical and structural analyses provide insights into the mechanism of both VPS34 complexes recruitment to and activation on membranes by specific Rab GTPases.